Islamic Microfinance Innovation: BMT Strategies for Enhancing Financial Inclusion and Economic Empowerment - Affandi, Ahmad Zulkifli; Syatar, Abdul; Sapa, Nasrullah Bin (JURNAL EKONOMI SYARIAH, 2025)
Baitul Mal wa Tamwil (BMT), as an Islamic microfinance institution, plays a pivotal role in providing fair and inclusive financial access to micro, small, and medium enterprises (MSMEs) in Indonesia. This study aims to comprehensively analyze the functions, product variations, and socio-economic roles of BMT, while also identifying the opportunities and challenges for BMT development in the modern era. Employing a qualitative descriptive approach through literature review, this research examines various sources related to Islamic microfinance and BMT. The analysis reveals that BMT not only serves as a provider of Sharia-compliant financing and manager of religious social funds, but also acts as an agent of community economic empowerment. In the digital era, BMT has significant opportunities to expand its services through product innovation and technology integration; however, it also faces challenges such as limited human resources, the need for stronger governance, and adaptation to evolving regulations and technologies. These findings highlight the importance of enhancing institutional capacity, strengthening Sharia financial literacy, and fostering collaboration with various stakeholders to optimize BMT’s role in supporting community economic empowerment and advancing sustainable Islamic financial inclusion.